Preparation method of cobalt-zinc-based electronic inverted perovskite nitride material and application of cobalt-zinc-based electronic inverted perovskite nitride material in photo-thermal catalysis of carbon monoxide oxidation
Through the preparation and application of cobalt-zinc-based electron inverted perovskite nitride materials, the problems of high cost and high energy consumption of precious metal catalysts in traditional catalytic combustion technology are solved, and the efficient and low-cost photothermal catalytic carbon monoxide oxidation effect is achieved. Meets the solar-powered carbon monoxide removal needs.
Patent Information
- Application Number
- CN202411385731.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Traditional catalytic combustion technology is used to remove precious metal catalysts in carbon monoxide. It is costly and energy-consuming, and requires high temperature conditions, making it difficult to meet actual use needs.
The preparation method of cobalt-zinc-based electron inverted perovskite nitride material is adopted, and the cobalt-zinc bimetallic precursor is obtained by room temperature stirring, ultrasonic dispersion and vacuum drying. Then, nitriding is performed in a nitrogen atmosphere to prepare a high thermal stability and a cobalt-zinc-based electron inverted perovskite nitride material with full spectrum light absorption capacity, used as a catalyst for photothermal catalyzing carbon monoxide oxidation.
The carbon monoxide conversion rate under full spectrum sunlight is achieved by nearly 100%, and efficient catalytic performance is maintained for a long time, reducing energy consumption and cost and meeting actual use needs.
Smart Images

Figure CN119259098A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photothermal catalytic materials, and specifically relates to a preparation method of a cobalt-zinc-based electron inversion perovskite nitride material and its application in photothermal catalytic carbon monoxide oxidation. Background Art
[0002] Carbon monoxide (CO) is a colorless, odorless gas that is dangerous in the environment due to its concealment. It is mainly derived from incomplete combustion of fossil fuels such as coal, oil and natural gas, and is also closely related to transportation and industrial emissions. Whether it is automobile exhaust or factory exhaust, the release of carbon monoxide can have a negative impact on air quality. Due to its serious threat to human health, such as headaches, dizziness and even fatal poisoning, the effective removal of carbon monoxide in the environment has become an important issue of global concern.
[0003] Traditional catalytic combustion technology is one of the main methods currently widely used for carbon monoxide removal. This technology relies on precious metal catalysts (such as platinum and palladium) to convert carbon monoxide into carbon dioxide by promoting the reaction of carbon monoxide with oxygen at high temperatures. Catalytic combustion can not only quickly and effectively reduce the concentration of carbon monoxide, but also reduce the emission of other harmful substances to a certain extent. However, despite the relatively high efficiency of catalytic combustion, its application is limited by the scarcity and high cost of precious metal resources. In addition, these catalytic reactions usually need to be carried out under high temperature conditions, which not only increases energy consumption, but may also bring economic burdens, while also affecting environmental friendliness, making it difficult to meet actual usage needs. Summary of the invention
[0004] To solve the above problems, the present invention proposes a preparation method of a cobalt-zinc-based electron-inverted perovskite nitride material and its application in photothermal catalytic carbon monoxide oxidation. The preparation method of the invention has a simple process, readily available raw materials, low cost and good reproducibility. The prepared cobalt-zinc-based electron-inverted perovskite nitride material has the advantages of high material thermal stability, light absorption capacity covering the entire solar spectrum and efficient photothermal conversion.
[0005] The present invention adopts the following technical solutions:
[0006] A method for preparing a cobalt-zinc-based electron inversion perovskite nitride material comprises the following steps:
[0007] S1. Add cobalt salt and zinc salt to ethanol and stir them thoroughly at room temperature to obtain a mixed solution;
[0008] S2, ultrasonically dispersing the mixed solution, and then transferring it to a vacuum constant temperature oven for vacuum drying, and after drying, a cobalt-zinc bimetallic precursor of a cobalt-zinc-based electron inversion perovskite nitride material can be obtained;
[0009] S3. Place the cobalt-zinc bimetallic precursor material in a tubular furnace, perform nitridation treatment in an ammonia atmosphere with a certain flow rate during programmed heating, and then introduce nitrogen during cooling to naturally cool to room temperature to obtain a cobalt-zinc-based electron inversion perovskite nitride material.
[0010] Preferably, the cobalt salt in step S1 is one or more of cobalt nitrate, cobalt acetate and cobalt chloride.
[0011] Preferably, the zinc salt in step S1 is one or more of zinc nitrate, zinc acetate and zinc chloride.
[0012] Preferably, in step S1, the molar ratio of the cobalt salt to the zinc salt is (2-4):1, the amount of ethanol used is 60-100 ml, and the stirring rate is 400-1000 r / min.
[0013] Preferably, in step S2, the ultrasonic dispersion time is 20-60 min, the vacuum drying time is 500-800 min, and the drying temperature is 70-90°C.
[0014] Preferably, in step S3, the purity of ammonia is ≥98%, the purity of nitrogen is ≥98%, the flow rate of ammonia is 10-60 mL / min, and the flow rate of nitrogen is 10-60 mL / min; the nitriding temperature is 550-650° C., and the nitriding time is 6-10 h.
[0015] A cobalt-zinc-based electron-inverted perovskite nitride material is prepared by the method for preparing the cobalt-zinc-based electron-inverted perovskite nitride material; the cobalt-zinc-based electron-inverted perovskite nitride material has a chemical formula of ZnNCo3 and has a cubic crystal phase. In the crystal structure, N and Co coordinate to form an octahedron, N is at the center of the octahedron, Co is at the vertex of the octahedron, and Zn is distributed in the gaps between the [NCo6] octahedrons.
[0016] An application of a cobalt-zinc-based electron inversion perovskite nitride material, wherein the cobalt-zinc-based electron inversion perovskite nitride material is used as a catalyst for photothermal catalytic carbon monoxide oxidation, and the catalytic conditions are: a mobile photothermal catalytic evaluation device is used, the light source is a xenon lamp, the reaction atmosphere is 1% CO+1% O2+98% Ar, the mixed gas flow rate is 30 ml / min, and the light intensity is 0.4-1.1 W / cm 2 , the amount of catalyst ZnNCo3 used is 50 mg.
[0017] After adopting the above technical solution, the present invention has the following advantages compared with the background technology:
[0018] 1. The present invention provides a method for preparing a cobalt-zinc-based electron-inverted perovskite nitride material. The preparation method has a simple process, readily available raw materials, low cost and good reproducibility. The prepared cobalt-zinc-based electron-inverted perovskite nitride material has the advantages of high material thermal stability, light absorption capacity covering the entire solar spectrum, and efficient photothermal conversion.
[0019] 2. The present invention applies the prepared cobalt-zinc-based electron-inverted perovskite nitride ZnNCo3 to the photothermal catalytic carbon monoxide oxidation reaction, and achieves a carbon monoxide conversion rate of nearly 100% and long-term photothermal catalytic reaction stability under full-spectrum solar illumination, which can realize the rapid conversion of carbon monoxide toxic gas driven by solar energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the cobalt-zinc-based electron inversion perovskite nitride material ZnNCo3 prepared in Example 1 of the present invention;
[0021] Figure 2 The cobalt-zinc-based electron-inverted perovskite nitride material ZnNCo3 prepared in Example 1 of the present invention and the X-ray diffraction pattern of the material after reacting in the reaction atmosphere for 1 day;
[0022] Figure 3 The crystal structure diagram of the cobalt-zinc-based electron-inverted perovskite nitride material ZnNCo3 prepared in Example 1 of the present invention;
[0023] Figure 4 The X-ray photoelectron spectrum of the cobalt-zinc-based electron inversion perovskite nitride material ZnNCo3 prepared in Example 1 of the present invention;
[0024] Figure 5 This is an ultraviolet absorption spectrum of the cobalt-zinc-based electron-inverted perovskite nitride material ZnNCo3 prepared in Example 1 of the present invention;
[0025] Figure 6 This is a performance diagram of the carbon monoxide conversion rate of the cobalt-zinc-based electron-inverted perovskite nitride material ZnNCo3 prepared in Example 1 of the present invention when applied to the photothermal catalytic carbon monoxide oxidation reaction at different light intensities;
[0026] Figure 7 The cobalt-zinc-based electron-inverted perovskite nitride material ZnNCo3 prepared in Example 1 of the present invention is applied to the long-term stable performance of the photothermal catalytic carbon monoxide oxidation reaction. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0028] See also Figures 1 to 7 .
[0029] Example 1
[0030] A method for preparing a cobalt-zinc-based electron inversion perovskite nitride material (ZnNCo3) comprises the following steps:
[0031] S1. Weigh 3 mmol of cobalt nitrate hexahydrate and 1 mmol of zinc nitrate hexahydrate, dissolve them in 80 ml of ethanol, stir at room temperature at a speed of 600 r / min for 30 min, mix and dissolve them thoroughly, and obtain a mixed solution;
[0032] S2. After the stirring is completed, the obtained mixed solution is ultrasonically dispersed for 30 minutes, and then transferred to a vacuum constant temperature oven at 80° C. for drying for 12 hours, and after drying, a cobalt-zinc bimetallic precursor of a cobalt-zinc-based electron inversion perovskite nitride material is obtained;
[0033] S3. Place the cobalt-zinc bimetallic precursor in a tubular furnace, extract the air in the tubular furnace with a vacuum pump, then introduce argon to normal pressure, repeat the pumping and purging three times, introduce high-purity ammonia, adjust the ammonia flow rate to 60 ml / min, increase the temperature to 600°C at a heating rate of 10°C / min and maintain for 10 hours, then introduce 60 ml / min of nitrogen during the cooling process and naturally cool to room temperature to obtain a cobalt-zinc-based electron inversion perovskite nitride material.
[0034] Example 2
[0035] A method for preparing a cobalt-zinc-based electron inversion perovskite nitride material (ZnNCo3) comprises the following steps:
[0036] S1. Weigh 3 mmol of cobalt acetate tetrahydrate and 1 mmol of zinc acetate dihydrate, then dissolve them in 80 ml of ethanol, stir at room temperature at a speed of 600 r / min for 30 min, mix and dissolve them thoroughly, and obtain a mixed solution;
[0037] S2. After the stirring is completed, the obtained mixed solution is ultrasonically dispersed for 30 minutes, and then transferred to a vacuum constant temperature oven at 80° C. for drying for 12 hours, and after drying, a cobalt-zinc bimetallic precursor of a cobalt-zinc-based electron inversion perovskite nitride material is obtained;
[0038] S3. Place the cobalt-zinc bimetallic precursor in a tubular furnace, extract the air in the tubular furnace with a vacuum pump, then introduce argon to normal pressure, repeat the pumping and purging three times, introduce high-purity ammonia, adjust the ammonia flow rate to 60 ml / min, increase the temperature to 600°C at a heating rate of 10°C / min and maintain for 10 hours, then introduce 60 ml / min of nitrogen during the cooling process and naturally cool to room temperature to obtain a cobalt-zinc-based electron inversion perovskite nitride material.
[0039] Example 3
[0040] A method for preparing a cobalt-zinc-based electron inversion perovskite nitride material (ZnNCo3) comprises the following steps:
[0041] S1. Weigh 3 mmol of cobalt nitrate hexahydrate and 1 mmol of zinc acetate dihydrate, then dissolve them in 80 ml of ethanol, stir at room temperature at a speed of 600 r / min for 30 min, mix and dissolve them thoroughly, and obtain a mixed solution;
[0042] S2. After the stirring is completed, the obtained mixed solution is ultrasonically dispersed for 30 minutes, and then transferred to a vacuum constant temperature oven at 80° C. for drying for 12 hours, and after drying, a cobalt-zinc bimetallic precursor of a cobalt-zinc-based electron inversion perovskite nitride material is obtained;
[0043] S3. Place the cobalt-zinc bimetallic precursor in a tubular furnace, extract the air in the tubular furnace with a vacuum pump, then introduce argon to normal pressure, repeat the pumping and purging three times, introduce high-purity ammonia, adjust the ammonia flow rate to 60 ml / min, increase the temperature to 600°C at a heating rate of 10°C / min and maintain for 10 hours, then introduce 60 ml / min of nitrogen during the cooling process and naturally cool to room temperature to obtain a cobalt-zinc-based electron inversion perovskite nitride material.
[0044] Example 4
[0045] A method for preparing a cobalt-zinc-based electron inversion perovskite nitride material (ZnNCo3) comprises the following steps:
[0046] S1. Weigh 3 mmol of cobalt chloride hexahydrate and 1 mmol of zinc chloride, then dissolve them in 80 ml of ethanol, stir at room temperature at a speed of 600 r / min for 30 min, mix and dissolve them thoroughly, and obtain a mixed solution;
[0047] S2. After the stirring is completed, the obtained mixed solution is ultrasonically dispersed for 30 minutes, and then transferred to a vacuum constant temperature oven at 80° C. for drying for 12 hours, and after drying, a cobalt-zinc bimetallic precursor of a cobalt-zinc-based electron inversion perovskite nitride material is obtained;
[0048] S3. Place the cobalt-zinc bimetallic precursor in a tubular furnace, extract the air in the tubular furnace with a vacuum pump, then introduce argon to normal pressure, repeat the pumping and purging three times, introduce high-purity ammonia, adjust the ammonia flow rate to 60 ml / min, increase the temperature to 600°C at a heating rate of 10°C / min and maintain for 10 hours, then introduce 60 ml / min of nitrogen during the cooling process and naturally cool to room temperature to obtain a cobalt-zinc-based electron inversion perovskite nitride material.
[0049] The SEM image of the cobalt-zinc-based electron inversion perovskite nitride material ZnNCo3 obtained in Example 1 is as follows: Figure 1 As shown, the sample is a sheet-like structure composed of hundreds of nanoparticles with a size between 100-200nm.
[0050] The X-ray diffraction test of the cobalt-zinc-based electron inversion perovskite nitride material ZnNCo3 obtained in Example 1, Example 2, Example 3 and Example 4 showed the same test effect. Taking the XRD of the cobalt-zinc-based electron inversion perovskite nitride material ZnNCo3 obtained in Example 1 as an example, Figure 2 As shown, the ZnNCo3 prepared by the above method exhibits good crystallinity. In addition, the XRD of the material has basically no change after one day of reaction in the reaction atmosphere, indicating that ZnNCo3 has good stability in the reaction atmosphere. The crystal structure of the cobalt-zinc-based electron inversion perovskite nitride material ZnNCo3 is shown in FIG. Figure 3 As shown, ZnNCo3 has a cubic crystal phase. In the crystal structure, N and Co coordinate to form an octahedron, N is at the center of the octahedron, Co is at the vertex of the octahedron, and Zn is distributed in the gaps between the [NCo6] octahedrons.
[0051] The X-ray photoelectron spectrum of the cobalt-zinc-based electron inversion perovskite nitride material ZnNCo3 obtained in Example 1 is as follows: Figure 4 As shown, the main peak of Zn 2p in ZnNCo3 can be decomposed into 2p 1 / 2 and 2p 3 / 2 , located at 1044.48eV and 1021.44eV respectively, while the Co element is mainly Co 3+ and Co 2+ The presence of. XRD and XPS tests further confirmed that the present invention successfully synthesized the cobalt-zinc-based electron inversion perovskite nitride material ZnNCo3.
[0052] The ultraviolet absorption spectrum of the cobalt-zinc-based electron inversion perovskite nitride material ZnNCo3 obtained in Example 1 is as follows: Figure 5 As shown, ZnNCo3 has good absorption in the entire spectrum and exhibits excellent photothermal properties.
[0053] The cobalt-zinc-based electron-inverted perovskite nitride material ZnNCo3 obtained in Example 1 was applied to the photothermal catalytic carbon monoxide oxidation reaction. A flow-type photothermal catalytic evaluation device was used to weigh 50 mg of the catalyst into a reaction tube, and the carbon monoxide conversion rate of the carbon monoxide oxidation reaction catalyzed by the device under different light intensities was tested. Figure 6 It can be seen that as the light intensity increases, the carbon monoxide conversion rate gradually increases. When the light intensity is 1.1W / cm 2 When the carbon monoxide conversion rate of ZnNCo3 can reach 100%, it shows excellent performance of photothermal catalytic carbon monoxide oxidation reaction; and the long-term performance of ZnNCo3 is also tested. Figure 7 It can be seen that ZnNCo3 can still maintain a 100% carbon monoxide conversion rate after 168 hours, indicating that it has good stability as a photothermal catalytic material in the carbon monoxide oxidation reaction.
[0054] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a cobalt-zinc-based electron inversion perovskite nitride material, characterized in that: The steps include: S1. Add cobalt salt and zinc salt to ethanol and stir them thoroughly at room temperature to obtain a mixed solution; S2, ultrasonically dispersing the mixed solution, and then transferring it to a vacuum constant temperature oven for vacuum drying, and after drying, a cobalt-zinc bimetallic precursor of a cobalt-zinc-based electron inversion perovskite nitride material can be obtained; S3. Place the cobalt-zinc bimetallic precursor material in a tubular furnace, perform nitridation treatment in an ammonia atmosphere with a certain flow rate during programmed heating, and then introduce nitrogen during cooling to naturally cool to room temperature to obtain a cobalt-zinc-based electron inversion perovskite nitride material.
2. The method for preparing a cobalt-zinc-based electron inversion perovskite nitride material according to claim 1, characterized in that: The cobalt salt in step S1 is one or more of cobalt nitrate, cobalt acetate and cobalt chloride.
3. The method for preparing a cobalt-zinc-based electron inversion perovskite nitride material according to claim 1, characterized in that: The zinc salt in step S1 is one or more of zinc nitrate, zinc acetate and zinc chloride.
4. The method for preparing a cobalt-zinc-based electron inversion perovskite nitride material according to claim 1, characterized in that: In step S1, the molar ratio of the cobalt salt to the zinc salt is (2-4):1, the amount of ethanol used is 60-100 ml, and the stirring rate is 400-1000 r / min.
5. The method for preparing a cobalt-zinc-based electron inversion perovskite nitride material according to claim 1, characterized in that: In step S2, the ultrasonic dispersion time is 20-60 min, the vacuum drying time is 500-800 min, and the drying temperature is 70-90°C.
6. The method for preparing a cobalt-zinc-based electron inversion perovskite nitride material according to claim 1, characterized in that: In step S3, the purity of ammonia is ≥98%, the purity of nitrogen is ≥98%, the flow rate of ammonia is 10-60 mL / min, and the flow rate of nitrogen is 10-60 mL / min; the nitriding treatment temperature is 550-650° C., and the nitriding treatment time is 6-10 h.
7. A cobalt-zinc-based electron-inverted perovskite nitride material, characterized in that: The cobalt-zinc-based electron-inverted perovskite nitride material is prepared by the preparation method of any one of claims 1 to 6; the cobalt-zinc-based electron-inverted perovskite nitride material has a chemical formula of ZnNCo3, has a cubic crystal phase, and in the crystal structure, N and Co coordinate to form an octahedron, N is at the center of the octahedron, Co is at the vertex of the octahedron, and Zn is distributed in the gaps between the [NCo6] octahedrons.
8. An application of the cobalt-zinc-based electron inversion perovskite nitride material as claimed in claim 7, characterized in that: The cobalt-zinc-based electron inversion perovskite nitride material is used as a catalyst for photothermal catalytic carbon monoxide oxidation. The catalytic conditions are: a mobile photothermal catalytic evaluation device is used, the light source is a xenon lamp, the reaction atmosphere is 1% CO+1% O2+98% Ar, the mixed gas flow rate is 30ml / min, and the light intensity is 0.4-1.1W / cm 2 , the amount of catalyst ZnNCo3 used is 50 mg.
Citation Information
Patent Citations
Method for preparing carbon nano-tube by in situ chemical vapour deposition method with nickel / titanium as catalyst
CN101279729A
CuNCo3 type electrocatalytic oxygen evolution catalyst with anti-perovskite structure and preparation method of CuNCo3 type electrocatalytic oxygen evolution catalyst
CN109638305A
Preparation and application of carbon-supported bimetallic nitride electrocatalyst
CN111224114A
Preparation Method and Use of Cobalt Nanoparticle / Boron Nitride Composite
US20230264179A1